2022
DOI: 10.1186/s12889-022-14170-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor self-reported health and unmarried status among adults: examining the hypothesis of marriage protection and marriage selection in the Indian context

Abstract: Background The link between marital status and health differences has long been a topic of debate. The substantial research on marriage and health has been conducted under two important hypotheses: marital protection and marriage selection. While the majority of evidence on the marriage-health relationship using these hypotheses comes from developed countries, there is a lack of evidence from Asia, particularly from India. Objectives The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Regarding marital status, the likelihood of poor SRH was significantly higher among the currently unmarried people than their counterparts in India. The result is similar to many previous studies in India and elsewhere [ 18 , 38 ]. The theory of marriage protection and selection explains the linkage between marital status and health outcomes, which supports our study findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding marital status, the likelihood of poor SRH was significantly higher among the currently unmarried people than their counterparts in India. The result is similar to many previous studies in India and elsewhere [ 18 , 38 ]. The theory of marriage protection and selection explains the linkage between marital status and health outcomes, which supports our study findings.…”
Section: Discussionsupporting
confidence: 92%
“…Existing literature suggests that marital status and living arrangements are significant social determinants of self-rated health in later life in India and other countries [ 17 ]. Many previous studies found a significant association between marital status and health outcomes among older people in India and elsewhere [ 18 ]. The positive and negative association varies with the geriatric population's space, place, and background characteristics [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies [ 7 , 12 ], with those having a spouse exhibiting higher cognitive functioning. The ‘marriage protection effect’ highlights that being married can affect the health level and longevity of individuals by providing emotional support and related social support from their spouses and promoting a healthy lifestyle [ 47 ], indicating that marital status enhances cognitive functioning in older people. This finding also supports the marriage resource model, which proposes that marriage offers multiple forms of resources for individuals with a spouse [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that marital status has an impact on both mental and physical health of older adults (e.g., Pettee et al, 2006; Sjöberg et al, 2020; Zhang & Li, 2011). In accordance with the marital protection hypothesis, older adults receive better attention and care within a marriage, and even protection from physical limitations (Hossain & James, 2022). Furthermore, marital relationships provide internal stability and support for individuals during later life, a time that can include many external changes, declines and losses (Bontinen, 2001).…”
Section: Introductionmentioning
confidence: 96%